2000
DOI: 10.1053/rapm.2000.8934
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epidural injection on spinal block during combined spinal and epidural anesthesia for cesarean delivery

Abstract: We could not achieve satisfactory surgical analgesia with 8 mg of hyperbaric bupivacaine injected into the subarachnoid space using the needle-through-needle technique in cesarean deliveries. An epidural saline injection elevated the sensory level, which did not improve the spinal block, whereas an epidural injection of 10 mL of 0.25% bupivacaine enhanced the spinal block and sustained the block postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 31 publications
0
23
1
Order By: Relevance
“…In most clinical trials on the subject of EVE conducted in nonobstetric patients, the volume of epidural injectate used is 10 mL;[781718] while in obstetric patients it ranges from 5[1920] to 10 mL. [25621] Higher volumes of 15 and 20 mL have also been evaluated in nonobstetric patients in a recent study in nonobstetric patients. [8]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most clinical trials on the subject of EVE conducted in nonobstetric patients, the volume of epidural injectate used is 10 mL;[781718] while in obstetric patients it ranges from 5[1920] to 10 mL. [25621] Higher volumes of 15 and 20 mL have also been evaluated in nonobstetric patients in a recent study in nonobstetric patients. [8]…”
Section: Discussionmentioning
confidence: 99%
“…[4] However, the minimum effective volume (MEV) of normal saline required to produce a rapid increase in the sensory level has not been investigated. In previously published studies on the subject of EVE, the volume of normal saline used for EVE ranges from 5 to 20 m,[3567] but there is very little data comparing the effect of various volumes of normal saline on the sensory block level per se . [38]…”
Section: Introductionmentioning
confidence: 99%
“…). Fifteen studies reporting on 1177 patients were considered eligible for quantitative analysis. The risk of bias assessment of the included studies is given in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Nine trials included parturients undergoing caesarean section , and six trials reported on other surgical procedures . In 12 out of 15 studies , the same anaesthetic mixture was used in the treatment and control arms. In three studies , all on caesarean section, a lower spinal anaesthetic dose plus epidural volume extension was applied in one group (epidural volume extension group) compared with a higher spinal anaesthetic dose without epidural volume extension (control group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation